The Barriers of Knowledge Acquisition and Knowledge Transfer in Software Companies: A Systematic Literature Review - Ersha Aisyah Elfaiz (Politeknik Negeri Cilacap, 2025)
Nowadays, organizations need computer-based information systems to improve their business process. Software company provide service to accommodate that needs. In the development process, knowledge acquisition and knowledge transfer are the most important process to understand the technology used. However, knowledge gap is a problem that may occur. To solve that, this research provides the barriers or problems that may occur in two process and the solutions. From the systematic literature review, we get 20 studies that relevant. Then, we know that knowledge acquisition barriers caused by human and organization. Knowledge transfer barriers caused by human, organization and technology. We also summarize the solution that proposed in the studies.